EFFECTIVE MECHANISMS OF FIGHTING SPIRITUAL-IDEOLOGICAL THREATS IN THE CONDITIONS OF GLOBALIZATION (American Journal of Pedagogical and Educational Research, 2024)
This article discusses globalization, ideological threat, popular culture, popular culture in the development of society, ideology.